2013
DOI: 10.1007/s10653-013-9515-1
|View full text |Cite
|
Sign up to set email alerts
|

Organic compounds in water extracts of coal: links to Balkan endemic nephropathy

Abstract: The Pliocene lignite hypothesis is an environmental hypothesis that has been proposed to explain the etiology of Balkan endemic nephropathy (BEN). Aqueous leaching experiments were conducted on a variety of coal samples in order to simulate groundwater leaching of organic compounds, and to further test the role of the Pliocene lignite hypothesis in the etiology of BEN. Experiments were performed on lignite coal samples from endemic BEN areas in Romania and Serbia, and lignite and bituminous coals from nonendem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 70 publications
1
35
0
2
Order By: Relevance
“…30,31 (However, see the Exposure Pathway is Unlikely section for contradictory results.) Also, greater numbers and higher concentrations of organic compounds were shown to be present in endemic vs nonendemic area water 39 and methanol 30,34 extracts of lignite samples. Furthermore, human mesenchymal stem cells exposed to a water extract of an endemic area Pliocene lignite showed increased cellular proliferation and differentiation compared to the control, 37 and human kidney cells exposed to concentrated high-molecular-weight organic compounds from an endemic village water sample showed excess cell death or proliferation compared to controls.…”
Section: Spatial Correlation Is Nothing More Than Fortuitousmentioning
confidence: 95%
See 3 more Smart Citations
“…30,31 (However, see the Exposure Pathway is Unlikely section for contradictory results.) Also, greater numbers and higher concentrations of organic compounds were shown to be present in endemic vs nonendemic area water 39 and methanol 30,34 extracts of lignite samples. Furthermore, human mesenchymal stem cells exposed to a water extract of an endemic area Pliocene lignite showed increased cellular proliferation and differentiation compared to the control, 37 and human kidney cells exposed to concentrated high-molecular-weight organic compounds from an endemic village water sample showed excess cell death or proliferation compared to controls.…”
Section: Spatial Correlation Is Nothing More Than Fortuitousmentioning
confidence: 95%
“…In addition, though some limitations have been addressed in the literature, information exists only in a piecemeal manner, e.g., in studies from 1991 16 to 2013. 39 Therefore, herein presented for the first time is a comprehensive compilation of the possible limitations of the hypothesis, with each limitation addressed in turn. The objective of this study was to systematically evaluate the role of the tenets of the Pliocene lignite hypothesis in the etiology of BEN in order to provide an improved understanding of the hypothesis for colleagues, patients, and those affected by the disease.…”
Section: This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…These outcomes relate to toxic organic compounds derived from coal, which can seep into water supplies, resulting in higher incidence of kidney disease in populations using untreated water as a water source (Orem, Tatu, Pavlovic, et al, 2007). Leaching tests on coal samples from Balkan Endemic Nephropathy areas found that there were more organic compounds than in other areas and the compounds existed in higher concentrations in the Balkan Endemic Nephropathy area coal samples compared to other coal samples (Maharaj, Orem, Tatu, Lerch, & Szilagyi, 2014).…”
Section: Water and Water Qualitymentioning
confidence: 99%